Crested 2D materials for optoelectronics and photonics. (September 2022) - Luo, Siwei; Guo, Gencai; Qi, Xiang; Liu, Weiyang; Tang, Han; Bao, Qiaoliang; Zhong, Jianxin
Abstract: To manipulate the electrical and optical properties of ultrathin two-dimensional (2D) layered materials, many approaches including the engineering of strain, doping, defects, and chemical absorption have been developed in recent years. However, the researches on crested substrates, which cause strains and emerging functionalities from the rigid substrate are limited. It shows great potential in improving carrier mobility, promoting charge transfer and charge injection, and decreasing the contact resistance of 2D material devices. Here, recent advances on crested substrates in 2D material-based optoelectronic and photonic devices are reviewed. These developments are classified in three aspects: the generation of crested structure in 2D materials; the strain-induced effect and more effects (plasmonic resonance, charge transfer, hot electron injection, optical effect) due to the crested surface; the state-of-the-art of the performance enhancement in 2D materials optoelectronics and photonics. We also present our perspectives on the physics and potential applications based on the crested structures.